2017
DOI: 10.21276/ijrdpl.2278-0238.2017.6(2).2517-2521
|View full text |Cite
|
Sign up to set email alerts
|

Speciation, biofilm formation and antifungal susceptibility of Candida isolates

Abstract: Abstract:Recently, an increase in the incidence of infections caused by fungi especially non-albicans Candida species has been reported. Several virulence factors like biofilm formation, toxin production and presence of adhesins contribute to its pathogenesis. This study was undertaken to determine species distribution, biofilm formation and in-vitro antifungal susceptibility of Candida isolated in our tertiary care hospital. One hundred and forty-two clinical isolates obtained from various clinical specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
2
1
0
Order By: Relevance
“…It was reported that some essential oils, as mentioned above, show potential inhibitory effects against Candida spp. biofilm by inhibiting hyphal formation, altering genes related to biofilm formation, or inhibiting adhesive proteins (Arora et al, 2017;Clark-Ordóñez et al, 2017;El-Baz et al, 2021). In the present research, we used relative cell viability and cell quantification by the MTT assay and qPCR, respectively, to demonstrate that M. fragrans oil has potent inhibition activity against C. albicans, which is in line with a previous report (Thileepan et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was reported that some essential oils, as mentioned above, show potential inhibitory effects against Candida spp. biofilm by inhibiting hyphal formation, altering genes related to biofilm formation, or inhibiting adhesive proteins (Arora et al, 2017;Clark-Ordóñez et al, 2017;El-Baz et al, 2021). In the present research, we used relative cell viability and cell quantification by the MTT assay and qPCR, respectively, to demonstrate that M. fragrans oil has potent inhibition activity against C. albicans, which is in line with a previous report (Thileepan et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Fluconazole inhibits the biosynthesis of ergosterol by interfering with lanosterol 14-α-demethylase activity to produce toxic 14-α-methyl-3,6-diol (Prasad et al, 2016). However, C. albicans resistance has been reported against fluconazole in recent years (Arora et al, 2017). To maintain its existence, C. albicans overexpress the ERG11 gene, which will upregulate the targeted enzyme and stimulate the efflux pump.…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal resistance in Candida species is important to track because it can provide information about new, emerging dangers from resistant strains of the disease that can aid in empirical treatment. In our analysis, all 148 of the isolates of Candida were found to be amphotericin B susceptible, which is consistent with the findings published by Arora et al 33 . According to…”
Section: Df=differencesupporting
confidence: 93%
“…The result of the present study (43.39%) are nearby Palwa et al (24.5%) where as lower prevalence was shown by Gandhi and Patel (7.14%), Arora et al (9.36%). [10][11][12] In the present study, C. albicans (45.3%) showed higher prevalence followed by C. tropicalis, (20.75%), C. glabrata (16.98%), C. parapsilosis (13.20%) and C. krusei (3.77%)(Table 2).…”
Section: Discussionsupporting
confidence: 50%